BEAUTY AND THE BEAST - Condon, Bill; Hoberman, David; Lieberman, Todd; Watson, Emma; Stevens, Dan; Evans, Luke; Kline, Kevin; Gad, Josh; McGregor, Ewan; Tucci, Stanley; McDonald, Audra; Mbatha-Raw, Gugu; et al. ([California] : [Walt Disney Pictures], 2017)
The journey of Belle, a bright and independent young woman who takes her father's place as the prisoner of a beast in his castle. As Belle befriends the castle's enchanted staff, she and the Beast slowly begin to look beyond their initial reactions to each other and see who they truly are. But back in Belle's village, her father's fears for her safety drive him to rally the villagers to free Belle from the castle--a plan that goes awry, with dangerous consequences, when Belle's would-be suitor Gaston twists the rally into a mob and leads an attack on the castle.
1080p high definition widescreen (2.40:1).
Song arranged and conducted by Michael Kosarin ; score arranged by Christopher Benstead ; music producer Matt Sullivan ; songs music by Alan Menken ; lyrics by Howard Ashman, Tim Race ; score by Alan Menken ; costume designer Jacqueline Durran ; edited by Virginia Katz ; production designer Sarah Greenwood ; director of photography Tobias Schliessler ; executive producers Jeffrey Silver, Thomas Schumacher, Don Hahn ; screenplay by Stephen Chbosky, Evan Spiliotopoulos.
Emma Watson, Dan Stevens, Luke Evans, Kevin Kline, Josh Gad, Ewan McGregor, Stanley Tucci, Audra McDonald, Gugu Mbatha-Raw, Ian McKellen, Emma Thompson.
U (General).
Blu-ray disc.
In English, Korean, Portuguese (Brazil), Thai and Chinese (Mandarin PRC) ; with English ESL, Bahasa Indonesia, Cantonese, Chinese (Mandarin Simplified), Chinese (Mandarin Traditional), Korean, Portuguese (Brazil) and Thai subtitles.
Keywords: Blessing and cursing -- Drama; Man-woman relationships -- Drama; Ugliness -- Drama